Niti Sataka Text (Ethical Education Perspective) - Edi Putra, I Nyoman Suarjaya; Perni, Ni Nyoman (International Journal of Multidisciplinary Sciences, 2024)
One of the efforts made to re-explore Susastra texts is the Niti Sataka text because the Niti Sataka text discusses 100 Shlokas about ethics and morals. Before practicing ethics in the community, it is better to apply it daily at home or with their family. These two words have a relationship with each other. In meaning, ethics and morals are often interpreted as the same even though they are different. Ethics are moral philosophy, while morals are our good and bad behavior. For example, Hinduism does not allow killing. Morally, it is not justified but can be justified ethically, such as killing animals for sacrifice during the war. In the Niti Sataka book, one of the teachings is that every educator needs to pay attention to students as they pay attention to their own children. Creating intelligence for all students is the main task of educators. Ethical and moral education is essential and related to one another because ethical education is related to human behavior or actions, namely good and bad deeds. In comparison, moral education makes humans moral or humane, especially in attitudes and how their daily behavior. Based on the explanation above, this study examined (1) what is the structure of the Niti Sataka text, (2) what are the main points of Hindu teachings in the Niti Sataka text, and (3) what is the form of ethical education in the Niti Sataka text. The theory used in analyzing the problem formulations was the theory of structuralism and the theory of hermeneutics. The type of research used was literature research. The method used in this study was the literature study method and the interview method. The study results indicated that (1) the structure of the Niti Sataka text is a shloka on ethics. The researcher chose several ethical shlokas, namely appropriate behavior, respecting good people, always doing good, helping selflessly, and being humble. (2) the main teachings of Hinduism in the text of Niti Sataka were manacika (thinking well), wacika (good speech), and kayika (good deeds). (3) the form of ethical education in the Niti Sataka text was descriptive ethics of ethics that can be seen critically and rationally in human attitudes and behavior and what human goals were precious in life. Normative ethics, attitudes, and behavior based on applicable norms or rules and ideal morality must be carried out by humans/society. Individual ethics, all things related to your daily life, will change according to your desires without being ordered by other people or your own family. According to all its dimensions, social ethics made humans aware of their responsibilities as humans in their lives as members of society.